Up-regulation of β-catenin in external auditory canal cholesteatoma - Naim, Ramin; Chang, Ray C.; Anders, Clemens Frithjof; Sadick, Haneen; Riedel, Frank; Bayerl, Christiane; Bran, Gregor M.; Hörmann, Karl (International journal of molecular medicine, 2005)
The external auditory canal cholesteatoma (EACC) is a rare disease with hyperproliferation and destructive growth in the adjacent structures. Down-regulation of β-catenin (key component of the zonula adherens) is a pivotal factor for loose tissue integrity and invasiveness. Transforming growth factor β1 (TGF-β1) was reported to decrease β-catenin in mammary epithelium. We investigated the abrogation of TGF-β1 and β-catenin expression in EACC culture cells. Cultured EACC-specimens were incubated with 6 µmol TGF-β1 antisense. After 48 h, expression of β-catenin was determined by means of immunohistochemistry. The cells showed an increased mural reactivity to β-catenin, and intracellular reactivity was unchanged. The untreated cells showed a loss of β-catenin expression at the membranes. The predominant membranous location after treatment with TGF-β1 antisense suggests increased tendency of the cells for tissue formation and strong cell-cell adhesion rather than migratory and invasive character, and thus TGF-β1 antisense application is a useful therapeutical strategy.